NOTARY OBLIGATIONS TO REPORT BENEFICIARIES OR BENEFICIAL OWNERSHIP (BO) IN EACH MAKING OF DEEDS - Endang Mastuti; Mispansyah Mispansyah; Ifrani Ifrani (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2023)
Abstract This study aims to analyze the urgency of the notary's obligation to report the beneficial owner in each deed to the Financial Transaction Analysis Reporting Center (PPATK) and how to assess the beneficial owner.Beneficial Ownership) referred to by the Legislation. The method used isnormative with the Antinomy research type, namely conflicting norms in the authority and obligations of a notary in reporting beneficial owners(beneficial ownership). The research results areThe urgency of the notary's obligation to report the beneficial owner(beneficial ownership) in each Deed to the Notary Financial Transaction Reports and Analysis Center (PPATK) as a state official or general official appointed by the state in making Deeds that are vulnerable to being exploited by money laundering (TPPU) and terrorism financing (TPPT) perpetrators.Authority The Financial Transaction Reports and Analysis Center (PPATK) requests reports from professions that are vulnerable to being misused by money laundering (TPPU) and terrorism financing (TPPT) perpetrators. PPATK asfinancial intelligence unit Whichhave duties and functions of receiving financial transaction reports, analyzing financial reports, and forwarding the results of the analysis to other law enforcement agencies. So the obligation to report the beneficial owner(beneficial owner) by a Notary to the Financial Transaction Reports and Analysis Center (PPATK) is very important and urgent in the prevention and eradication of money laundering (TPPU) and terrorism funding (TPPT) crimes